Challenges in neuropsychological improvement after shunt surgery for idiopathic normal pressure hydrocephalus - Rýdlo, Ondřej; Bubeníková, Adéla; Skalický, Petr; Häcklová, Klára; Leško, Robért; Vlasák, Aleš; Georgi, Hana; Bradáč, Ondřej (Frontiers in Aging Neuroscience, 2025)
ObjectivesTo evaluate cognitive and mood changes 3 months after shunting for idiopathic normal-pressure hydrocephalus (iNPH), and compare postoperative outcomes with matched healthy controls across cognitive domains.MethodsThirty-three iNPH patients underwent neuropsychological testing preoperatively and at 3 months; 71 age-, sex-, and education-matched controls were assessed once. Tests were grouped into six cognitive domains.ResultsShunting yielded significant gains in Verbal Memory and Psychomotor Pace; Executive Functions improved selectively. Non-Verbal Memory, Language, and Visuospatial Abilities showed no postoperative change. Depressive symptoms decreased significantly. However, at 3 months patients still performed worse than controls on all tests (all p < 0.001).ConclusionShunt surgery produces measurable yet domain-limited cognitive benefits in iNPH at 3 months, particularly in verbal learning and processing speed, alongside mood improvement. Performance remains below healthy norms, indicating partial recovery. Larger, prospective cohorts and longer follow-up are needed to determine durability, breadth of cognitive change, and predictors of response.